Analysis of the Potential Cost of Damage Due to Liquefaction on Two-Story Residential Buildings in North Jakarta - Farhan Heryo Nugroho; Muhammad Zaki (Eduvest - Journal of Universal Studies, 2026)
This study is motivated by the high seismic activity in Indonesia due to the interaction of three major tectonic plates, as well as the geological conditions of coastal areas such as North Jakarta, which are dominated by soft, water-saturated alluvial soils prone to liquefaction. This phenomenon can lead to severe structural damage and significant economic losses, particularly for two-story residential buildings. This research aims to analyze the liquefaction potential and estimate the economic losses caused by building damage in North Jakarta. The study employed a quantitative descriptive approach using Standard Penetration Test (N-SPT) data from 26 drilling points. Key geotechnical parameters, including Cyclic Stress Ratio (CSR), Cyclic Resistance Ratio (CRR), Magnitude Scaling Factor (MSF), and Safety Factor (SF), were calculated. Earthquake acceleration (amax) was also analyzed using Donovan, McGuire, and Matuschka methods. The results indicate that liquefaction potential increases with earthquake magnitude, with critical conditions occurring at a magnitude of 5.5 Mw, where all points experience liquefaction in shallow layers. Cilincing and Ancol are identified as the most vulnerable areas due to low N-SPT values and shallow groundwater levels. The estimated total economic loss reaches IDR 4.734 trillion, with per capita losses ranging from IDR 3.4 million to IDR 6.3 million. In conclusion, North Jakarta faces high liquefaction risk with substantial economic impacts, highlighting the need for mitigation strategies in urban planning and structural design.